Presentation of Suspected Pediatric Uveitis. (January 2014) - Saeed, Muhammad Usman; Raza, Syed Hamid; Goyal, Sudeshna; Cleary, Gavin; Newman, William David; Chandna, Arvind
Abstract Presentation of suspected pediatric uveitis: Pediatric uveitis is usually managed in specialized ophthalmic centers in the UK. Meaningful data acquisition in these clinics may be helpful in clinical governance, and healthcare planning in a specialty that is gradually changing due to changes in treatment choices. Methods: Retrospective analysis of prospectively acquired data in the Liverpool pediatric uveitis database was performed. Results: Analysis of our data, based on 147 patients, with a mean age of 10 years, indicated a female to male ratio of 2:1. 99% of patients were Caucasian. Our data indicates 86% of all patients attending the uveitis clinic were diagnosed with juvenile idiopathic arthritis, followed by intermediate uveitis 5% and idiopathic uveitis 4%. 46% of patients required treatment. Systemic treatment included methotrexate (34%), prednisolone (14%), etanercept (6%), ciclosporin (6%), mycophenolate (3%), and infliximab (1%). Severe visual loss (defined by counting fingers or below vision) was seen in 10 eyes despite appropriately treated chronic uveitis. Conclusion: Our data shows uveitis-related ocular morbidity in a predominantly pediatric Caucasian population. Patients with severe and chronic uveitis may experience significant uveitis-related complications and subsequent visual loss despite aggressive treatment.